First-principles calculations of the electronic properties of two-dimensional pentagonal structure XS2 (X=Ni, Pd, Pt). (April 2020) - Yang, Hongye; Li, Yinan; Yang, Zechen; Shi, Xiaoqin; Lin, Ziwei; Guo, Ruijuan; Xu, Lili; Qu, Hengze; Zhang, Shengli
Abstract: Two-dimensional (2D) transition metal dichalcogenides (TMDs) have aroused enormous interests due to their novel physical properties and wide ranges of potential applications. Recently, some metals sulfides with unique pentagonal configuration and electronic properties have attracted special attention. Herein, based on first-principles calculations, the stabilities, electronic structures and properties of three kinds of 2D TMDs with pentagons, namely monolayer non-novel and novel metal dichalcogenides NiS2, PdS2 and PtS2, have been theoretically studied. Compared with the other two materials, PtS2 is more stable with the cohesive energy of 5.01 eV/atom. The band gaps of NiS2, PdS2 and PtS2 are 0.87 eV, 1.08 eV and 2.01 eV, respectively. In addition, under biaxial strain, these materials were transformed from semiconductor to metal properties. The availability of tunable electronic properties provides exciting opportunities for designing artificial layered structures for applications in optoelectronics and flexible electronics. Graphical abstract: Image 1 Highlights: The pentagonal structure XS2 (X = Ni, Pd, Pt) are thermodynamic and kinetic stabilizable. The pentagonal structure XS2 (X = Ni, Pd, Pt) exhibits semiconductors with indirect band gaps. Under biaxial strain, the pentagonal XS2 (X=Ni, Pd, Pt) displays wide tunable properties from semiconductor to metallic.